Review of Technology Adoption Models and Theories to Measure Readiness and Acceptable Use of Technology in a Business Organization (Journal of Information Technology and Digital World, 2020)
It has been evident that innovative technologies have evolved in the past few decades, notably, in the computing discipline. As a result, technology adoption models and theories are deemed vital to business organizations to assess if end users are ready and accept new technologies. Therefore, requirements to review prevailing technology adoption models and theories which seek to assist business organizations to assess the readiness and acceptance of these new technologies, otherwise, such initiatives become obsolete and do not support core business processes, as it was originally intended. This paper reviews three technology adoption models relevant to information systems and information technology studies on the latest technologies such as ERP, cloud computing, and other systems implemented in business organizations. The study could assist to analyse the acceptance and utilization of new technologies. It can also be used to improve such models and theories in the adoption of new technologies.
Keywords: Technology adoption models; technology acceptance theories; technology acceptance model (TAM); technology-organization-environment (TOE); unified theory of acceptance and use of technology (UTAUT)